Transcriptional regulation of the human c-myc gene. - Lang, J. C. (Nature Publishing Group, 1988)
The involvement of c-myc in the genesis of animal neoplasia is now well documented for several systems. In order to define the precise role played by the myc gene in tumorigenesis, a better understanding of the normal regulation of myc expression is necessary. We have begun a study of the cis-acting regulatory sequences within the 5' flanking domain of the human c-myc gene. Regions important for myc promoter function have been identified by linkage to the coding sequences of the bacterial chloramphenicol acetyltransferase (cat) gene. Promoter deletion studies and in vivo competition assays for c-myc/cat recombinant plasmids have allowed the identification of a proximal 'core' promoter region capable of directing high levels of CAT activity. Further upstream a negative regulatory element (NRE2) has been identified which is capable of repressing cat gene expression and which functions by interaction with a transacting factor(s). Preliminary data suggests detection of NRE2 is dependent on both the type and amount of carrier DNA used in transient CAT assays. Initial experiments further indicate the involvement of at least two other distal regulatory domains, a negative regulatory domain (NRE1) and a putative enhancer-type region (E). In vitro footprint analysis has allowed the identification of DNA binding proteins which interact with NRE2 and the 'core' promoter. NRE2 contains binding sites for transcription factors Sp1 and CTF. The 'core' promoter domain appears to be highly complex and possesses several Sp1 binding sites.